Penerapan strategi promosi sekolah terhadap citra sekolah di masyarakat - Wulandari, Yunita; Z, M Mulky Fardhan; Darmawan, Abdu; Zuhriyah, Indah Aminatuz (Maliki Interdisciplinary Journal, 2024)
This research is motivated by the development of technology and the large number of schools today so that competition between schools is very tight in attracting students and parents to choose a school. The aim of this research is to explore various school promotion strategies from each school institution in Indonesia, through analyzing various promotional activities to attract prospective students and build an image in society. This research uses a qualitative approach by describing and explaining the implementation of school promotion strategies in building the public's image and interest in the school. How to describe and describe is done through several expert opinions. This research using a qualitative approach is expected to be able to provide comprehensive facts about the implementation of school promotion strategies in building the public's image and interest in schools. The data collection technique used in this research is library research. This technique is carried out by collecting study materials which can be sourced from books, scientific journals and authors with the aim of obtaining theoretical information so that researchers have a strong foundation for obtaining scientific results. The data obtained is used to strengthen the author's argument in analyzing the implementation of school promotion strategies. These findings will contribute to existing knowledge about marketing and promotion in the education sector.